Transvaginal versus transabdominal specimen extraction surgery for right colon cancer: A propensity matching study - Yu, Hongxin; Lu, Weijie; Zhong, Chonghan; Ju, Houqiong; Wu, Can; Xu, Haocheng; Liu, Dongning; Li, Taiyuan (Frontiers in Oncology, 2023)
Abstract Background The transvaginal route for specimen extraction is considered ideal for colorectal surgery, but its safety is still questioned, There has been little researches on transvaginal NOSES（natural orifice specimen extraction surgery） in the right hemicolectomy. As a result, we conducted a study comparing transvaginal NOSES to traditional transabdominal specimen extraction surgery. Patients and methods Data on female patients who underwent radical right hemicolectomy at the First Affiliated Hospital of Nanchang University between January 2015 and December 2020 were collected retrospectively. A total of 847 patients were compliant, with 51 undergoing transvaginal specimen extraction surgery (NOSES group) and 796 undergoing transabdominal specimen extraction surgery (TISES group). To balance the clinicopathological characteristics of the two groups, a propensity score matching method (1:2) was used. Results Finally, 138 patients were enrolled in our study, with 46 in the NOSES group and 92 in the TISES group. Compared to TISES group, The NOSES group had less intraoperative blood loss (p=0.036), a shorter time to first flatus (p<0.001), a shorter time to first liquid diet (p<0.001), lower postoperative white blood cell counts (p=0.026), lower C-reactive protein levels (p=0.027), and lower VAS scores (p<0.001). In regard to quality of life after surgery, NOSES group had better role function (p<0.01), emotional function (p<0.001), and better symptoms of postoperative pain (p<0.001) and diarrhea (p=0.024). The scar satisfaction was significantly higher in the NOSES group than in the TISES group. Overall survival and disease-free survival in two groups were similar. Conclusion The short-term results of transvaginal NOSES were superior to conventional transabdominal specimen extraction surgery, at the same time transvaginal NOSES can improve the abdominal wall appearance and quality of life. The long-term survival was similar in the two surgical approaches. Therefore, transvaginal NOSES is worthy of our implementation and promotion.